REDD+ PROJECT FEASIBILITY STUDY THROUGH FOREST MANAGEMENT SCHEME IN DIEN BIEN PROVINCE - Xuan Truong, Le (Journal of Forestry Science and Technology, 2016)
The feasibility study was conducted in Muong Phang, Na Nhan, and Na Tau communes, Dien Bien district, Dien Bien province. Based on GIS data and the satellite images of the forest coverage anlysis in three points of time in the past (1990, 2000, and 2010) and the results of the survey on the tree volume, tree growth, and tree increment in 6 typical plots of plantation, 15 typical plots of natural forest, and the socio-economic analysis three scenarios were proposed for the project area to the year 2040. Most of the natural forest in the project area were poor and rehabilitation forest. There was big area of bare land that was potential for forest rehabilitation and regeneration, both natural and manmade regenerations. Mean annual increment of plantation ranged from 3.83 m3/ha/year (Vernicia montana) to 11.27 m3/ha/year (Pinus massoniana). The volume of natural forest ranged from 11.6 m3/ha to 554.1 m3/ha. From the current forest coverage, the scenario, and the estimated biomass value change in future, used the method of IPCC to estimate the greenhouse gas (CO2) emissions/reduction. The Carbon stock was about 2,182,000 tons CO2 for scenario 1; about 1,592,000 tons CO2 for scenario 2; and was about 1,275,000 tons CO2 for scenario 3 for the project area.